Significance of eLearning at Sunway University: A perspective from Art and Design Students - Surarajah, Saravanamalar (Journal of Education and Vocational Research, 2015)
Online learning platforms give a great opportunity for various types of learners with different learning abilities to learn at their own pace anytime, anywhere and at any cost. Some of the most common online platforms are Moodle, Blackboard and Virtual Learning Environment (VLE). Each platform has its own impact to the learners. It can be a positive or negative impact depending on the content of the subject matter, layout, design and user friendliness of the course site. However, online platforms can be significant for many learners but not for all. This paper studies the significance of using Blackboard (known as eLearn at Sunway University) in teaching and learning at Department of Art and Design, Sunway University. 79 students at this department had participated in the survey and given their feedback on using eLearn and about 74.7% of them are local students and the rest are international students. Teaching mathematics online can be different from history; teaching spiritual values can be different from science. However, all online teachings and learnings have something in common. There are some factors that make the online facilitators rise and fall at times. This paper also discovers learners’ expectation for a better eLearn experience.